(untitled) (Al-Farooq Journal of Sciences, 2026)
This research aims to examine the semiotics of the cover in Tayeb Salih’s novel Season of Migration to the North. It begins by presenting the linguistic and terminological concepts of semiotics and tracing its development in both Arab and Western studies, before addressing the nature of the book cover and its significance within narrative texts. The research problem centers on identifying the meanings conveyed by the cover of Season of Migration to the North and exploring the relationship between these meanings and the events and content of the novel. It also seeks to demonstrate the impact of the cover image and the extent of its connection to the narrative text. The significance of the research lies in revealing the relationship between the syntactic and semantic structure of the title and the novel’s content in light of the semiotic approach. The research reached several findings, most notably that semiotics is one of the critical approaches concerned with the study of signs and their various types in narrative discourse. It also found that the title of Tayeb Salih’s Season of Migration to the North is closely connected to the content of the novel, as each complements and reinforces the other semantically. Furthermore, the title embodies the central idea around which the events are structured and constitutes a significant semiotic icon at both the syntactic and semantic levels. In addition, the cover image reflects the conflict between Western and Eastern traditions and illustrates the complex interrelationship between love and conflict through the protagonist’s complicated relationship with Western women.